2021
DOI: 10.1039/d1fo00671a
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota mediates the effects of curcumin on enhancing Ucp1-dependent thermogenesis and improving high-fat diet-induced obesity

Abstract: Due to extremely poor systemic bioavailability, the mechanism by which curcumin increases energy expenditure remains unelucidated. Accumulating evidence suggests a strong association between the gut microbiota (GM) and energy metabolism....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 51 publications
0
31
0
1
Order By: Relevance
“…They are produced in the liver and biochemically modified by intestinal bacteria. BA can act as signaling molecules in many tissues and influence host metabolism through signaling pathways through BA detecting receptors [ 46 ]. Among them, BAs have been found to increase the activity of BAT via G protein-coupled bile acid receptor 5 (TGR5) [ 47 ].…”
Section: Reciprocal Interaction Between Curcumin and Gut Microbiota (Gm)mentioning
confidence: 99%
See 2 more Smart Citations
“…They are produced in the liver and biochemically modified by intestinal bacteria. BA can act as signaling molecules in many tissues and influence host metabolism through signaling pathways through BA detecting receptors [ 46 ]. Among them, BAs have been found to increase the activity of BAT via G protein-coupled bile acid receptor 5 (TGR5) [ 47 ].…”
Section: Reciprocal Interaction Between Curcumin and Gut Microbiota (Gm)mentioning
confidence: 99%
“…Han et al [ 46 ] investigated whether GM mediates the effects of curcumin in improving energy homeostasis. For this purpose, mice fed a high-fat diet (HFD) uncoupling protein 1 (Ucp1) knockout and G protein-coupled membrane receptor 5 (TGR5) were used.…”
Section: Reciprocal Interaction Between Curcumin and Gut Microbiota (Gm)mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that Lactobacillus , a probiotic, can metabolise sugar into lactic acid and participate in the metabolism of Bile Acids (BA). Anaerotruncus produces butyric acid, which is associated with obesity ( 61 ). Roseburia produces SCFAs that are associated with obesity ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Curcumin could affect intestinal microbiota to prevent renal failure [6]. Conversely, intestinal microbiota could also enhance the effect of Curcumin in ameliorating HFDinduced obesity by enhancing Ucp1-dependent thermogenesis through regulating bile acids metabolism [8], suggesting the interaction between intestinal microbiota and Curcumin in curing diseases.…”
Section: Introductionmentioning
confidence: 99%